Verification of Resveratrol Inhibits Intestinal Aging by Downregulating ATF4/Chop/Bcl-2/Bax Signaling Pathway: Based on Network Pharmacology and Animal Experiment - Liu, Tian-hao; Tu, Wan-qing; Tao, Wen-cong; Liang, Qiu-er; Xiao, Ya; Chen, Li-guo (Frontiers in Pharmacology, 2020)
Resveratrol is one of the most well-known drugs used in the treatment of aging. However, the potential mechanisms of resveratrol on intestinal aging have not yet been fully investigated. Herein, we aimed to further explore the pharmacological mechanisms of resveratrol as a therapy for intestinal aging. We performed network construction and enrichment analysis via network pharmacology. Then a further animal experimental validation containing 20 female C57BL/6J (wild type, WT) and 16 female ATF4+/- (knock down, KD) naturally aging mice and oral supplementary resveratrol (44 mg/kg/d) for 30 days were conducted. The expression of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT), linear alkylethoxylate (AE) and malondialdehyde (MDA) were measured by ELISA, the observation of pathological changes and apoptosis in intestinal tissue were performed by HE, PAS and TUNEL staining, the ATF4/Chop/Bcl-2/Bax signaling pathway-related proteins and mRNAs expression were measured by western blotting and real-time PCR. The network pharmacology showed 132 targets of resveratrol on aging. The enrichment analysis showed resveratrol anti-aging involved mainly included protein heterodimerization activity, apoptosis, etc. Then ATF4/Chop/Bcl-2/Bax signaling pathway in biological process of apoptosis was selected to verify the potential mechanisms. Animal studies showed resveratrol upregulated the relative expression of SOD, GSH-Px, CAT, AE, whereas it downregulated the relative expression of MDA in intestine compared with the control group. There was also higher relative expression of SOD, GSH-Px, CAT, AE and lower relative expression of MDA in KD mice than that in WT mice. Moreover, there was higher relative expression of SOD, GSH-Px, CAT, AE and lower relative expression of MDA in KD mice than that in WT mice after resveratrol treatment. Decreased ATF4, Chop, Bax but increased Bcl-2 proteins and mRNAs expression were determined after resveratrol treatment compared with the control group; lower ATF4, Chop, Bax but higher Bcl-2 proteins and mRNAs expression were found in KD mice than that in WT mice. Additionally, lower relative proteins and mRNAs expression of ATF4, Chop, Bax and higher relative expression of Bcl-2 in KD mice than that in WT mice after resveratrol treatment. These findings demonstrated that resveratrol substantially inhibited intestinal aging via downregulating ATF4/Chop/Bcl-2/Bax signaling pathway.